Phytosociological notes on the Lygeum spartum grasslands from Crete - Brullo, Salvatore; Giusso del Galdo, Gianpietro; Guarino, Riccardo (Lazaroa, 2002)
Lygeum spartum grasslands from Crete have been studied by using the phytosocological approach. This type of pastures of Lygeo-Stipetalia tenacissimae (Lygeo-Stipetea class), are included into a new alliance named Scorzonero creticae-Lygeion sparti. Three new associations have been recognized: Limonio hyssopifolii-Lygeetum sparti, occuring on halomorphic badlands in the Sitia territory (NE Crete); Erodio crassifolii-Lygeetum sparti, growing on heavily eroded clayey outcrops eastward of Ierapetra (SE Crete); Convolvulo oleifolii-Lygeetum sparti, substituting the previous one on stratified marls mixed to conglomerates close to Makrigialos. Within the last association, two subassociations have been recognized: limonietosum roridi, grouping the aspects occurring near the sea, and fumanetosum laevipedis relative to the inland aspects. To evaluate the similarity among the relevés, a numerical multivariate analysis has been performed.